Managing Storable Commodity Risks: Role of Inventories and Financial Hedges - Kouvelis, Panos (Institutional Knowledge at Singapore Management University, 2013)
This paper studies the integrated operational and financial risk management of storable commodities, such as aluminum and steel, used as inputs in end-products with uncertain demand. In our dynamic mean-variance model, we study a problem of dual sourcing with financial hedging for a risk averse buyer (the seller of the end product) who procures a single storable commodity from a supplier via a fixed price, fixed quantity long-term contract and ``tops up" via short-term purchases from a spot market. The spot market has adequate supply (i.e., market liquidity is assumed) but a random price. To hedge the uncertainty of the spot price and the end-product customer demand, the buyer can trade financial contracts written on the spot market prices such as futures contracts, call and put options. We obtain multi-period optimal inventory and financial hedging policies for a risk averse buyer with an inter-period mean-variance objective. For most cases, the optimal policies are myopic and easy to compute and implement. We examine different cases of financial hedging, single hedges and portfolio hedges, and characterize their optimal hedging amounts and portfolio structure. For optimal portfolios (use of futures contracts and call/put options) the allocation of funds to the various hedges can be obtained via the solution of a system of linear equations. We also offer insights on the role and impact of the operational hedge (physical inventory) and financial hedge on the profitability, risk control, and service level to the customer.